IDENTIFY ACID-BASE WITH EXTRACT DRAGON FRUIT AND TURMERIC - Selly Tria Amanda; Difa Putri Miarta; Halimatus sa'diyah; Anis Rosalita; Sonny Kristianto (Jurusan Pendidikan Biologi, Fakultas Bahasa dan Sains, Universitas Wijaya Kusuma Surabaya, 2023)
This study aims to determine the identification of acid-bases with natural indicators. This, is done because acid-base testing uses a lot of litmus paper. In dragon fruit extract and turmeric extract, there is a more concentrated color pigment content to determine the acid-base concentration. So we want to increase its sensitivity to detecting acid- bases. The method used in this study is experimental. The results of the study can be used to assist the public in knowing the benefits of dragon fruit and turmeric to detect acid-base solutions.